Downregulation of hsa-miR-135b-5p Inhibits Cell Proliferation, Migration, and Invasion in Colon Adenocarcinoma. (21st October 2022) - Zhang, Yunxin; Zhang, Wentao; Xia, Wenlong; Xia, Junwei; Zhang, Haishan
Abstract : Colon cancer is the most common malignant tumor of the gastrointestinal tract, and approximately 80%–90% of colon cancers are colon adenocarcinomas (COADs). This study aimed to screen key microRNAs (miRNAs) associated with COAD. Differentially expressed (DE) miRNAs were screened between COAD and adjacent cancer samples based on the Gene Expression Omnibus (GEO) and the Cancer Genome Atlas obtained from datasets. The miRNAs of interest were validated using quantitative real-time polymerase chain reaction. Moreover, the effects of hsa-miR-135b-5p on the biological behavior of COAD cells were observed. To obtain the target genes of hsa-miR-135b-5p, transcriptome sequencing of the SW480 cells was performed, followed by protein-protein interaction (PPI) network and hsa-miR-135b-5p-target gene regulatory network construction and prognostic analysis. Downregulation of hsa-miR-135b-5p significantly inhibited SW480 cell proliferation, migration, and invasion and significantly facilitated apoptosis (P < 0.05). A total of 3384 DEmRNAs were screened, and enrichment analysis showed that the upregulated mRNAs were enriched in 25 Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways and 326 Gene Ontology Biological Processes (GO-BPs) while the downregulated mRNAs were enriched in 20 KEGG pathways and 276 GO-BPs. A PPI network was then constructed, and H2BC14, H2BC3, and H4C11 had a higher degree. In addition, a total of 352 hsa-miR-135b-5p-gene regulatory relationships were identified. Prognostic analysis showed that FOXN2, NSA2, MYCBP, DIRAS2, DESI1, and RAB33B had prognostic significance (P < 0.05). In addition, the validation analysis results showed that FOXN2, NSA2, and DESI1 were significantly expressed between the miR-135b-5p-inhibitor and negative control groups (P < 0.05). Therefore, downregulation of hsa-miR-135b-5p inhibits cell proliferation, migration, and invasion in COAD, and carcinogenesis may function by targeting FOXN2, NSA2, MYCBP, DIRAS2, DESI1, and RAB33B .